Pediatric sepsis and septic shock: definitions and treatment algorithms - Krastins, Jekabs (Acta medica Lituanica, 2012)
Sepsis remains one of the leading causes of morbidity and mortality in children despite improved understanding of the pathophysiology leading to better clinical management and survival. Recent studies have identified several areas that must be addressed by the clinician in order to continue to impact the morbidity and mortality associated with sepsis. In this review, we discuss the evidence in several of these areas including recognition of shock, initial resuscitation and fluid therapy, use of inotropes and vasopressors, identification and control of the source of infection, maintenance of oxygen delivery and ventilation. The overall goal is to provide the bedside clinician with an updated systematic approach to treat sepsis in children.